The Implementation of Good Corporate Governance at Sharia Rural Banks (BPRS): A Study of BPRS Sukowati Sragen - Shoffan Mujahid; Sabiq Muhammad Al Ghozi (Journal of Management and Islamic Finance, 2026)
This study aimed to analyse the implementation of GCG at BPRS Sukowati Sragen in order to determine the effectiveness of GCG in improving operational and Sharia compliance. The research method used is qualitative, involving a documentary analysis of BPRS Sukowati Sragen. Data collection was conducted through the analysis and study of documentation from annual reports obtained from the official BPRS website. The results of the study indicate that BPRS Sukowati Sragen implements GCG in accordance with its principles: Transparency, Accountability, Responsibility, Independence, and Fairness. These results answer the research question that BPRS, as an Islamic financial institution, should apply governance professionally. The significance of this study is to present quality governance at BPRS to prevent fraud and agency conflicts within the institution. Additionally, through this analysis, it can be determined which principles still need improvement to achieve governance quality that enhances the trust of customers and stakeholders involved. In addition, this analysis identifies the governance principles that still require improvement to achieve better governance quality. Therefore, the consistent implementation of GCG is essential not only for ensuring regulatory and Sharia compliance, but also for maintaining financial institution stability, protecting stakeholder interests, improving operational performance, and increasing the trust of customers and other stakeholders. Strong governance ultimately supports the sustainability, integrity, and competitiveness of BPRS in the Islamic banking industry.